Peran Self Efficacy Memoderasi Religiusitas, Dukungan Sosial dan Self Disclosure Terhadap Resiliensi Akademik - Shofi, Ezar; Khayati, Afif Nur; Kardiyem; Pujiati, Amin (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study aims to analyze the effect of religiosity, social support and self-disclosure on student academic resilience with self efficacy as a moderating variable. The population in this study were students of the economic education study program majoring in accounting education at Semarang State University class of 2020. The sampling technique used probability sampling with a sample size of 118 students. The data analysis method uses descriptive analysis and moderation regression analysis. The results showed that religiosity variables had a positive and significant effect on academic resilience, while social support and self-disclosure variables had no positive and significant effect on academic resilience. Self efficacy as a moderating variable can significantly strengthen the effect of religiosity on academic resilience but cannot strengthen the effect of social support and self-disclosure on academic resilience. Suggestions from this study students are expected to be able to increase faith in God, multiply worship, deepen religious knowledge, be able to be patient, be grateful and increase self-confidence to improve academic resilience.